Characteristics, significance and pathogenesis of atypical endometrial changes associated with the presence of chorionic tissue - Arias Stella, Javier (1959)
The histological features of atypical endometrial alterations we found in cases of uterine abortion, ectopic pregnancy, 44 cases described, hydatidiform mole, choriocarcinoma, destruens chorioadenoma, syncytial endometritis and normal uterine pregnancy, based on the study of 250 cases of uterine abortion, ectopic pregnancy, 32 cases of hydatidiform mole, 25 cases of chorionic, 6 cases of syncytial endometritis and 3 cases of apparently normal pregnancy.